Process of Entrance, Rising, Falling and Exit of Qhajar Tribe in the Diagram of Political Power - قباد منصوربخت; محمدمحمود هاشمی (پژوهش‌های تاریخی ایران و اسلام, 2012)
Power seekers in Iranian political history came mainly from tribal communities. When they gained power they would fall and then they were removed from the power unconsciously. Getting into a tribal life style, living in a colonized form and changed life style played an important role in weakening their power economically and intellectually. This necessarily leads to the emergence of a new figure and the seizure of  the power . Qhajar dynasty came to power in such a process; however their rising did not follow the said pattern, but a pattern which had no precedent in Iranian past history. The results of this research indicate that Qhajar dynasty was forced to accept military renovation, in spite of its resistance. Such a renovation paved the way for its fall.